Handbook on animal-assisted therapy : foundations and guidelines for animal-assisted interventions - Fine, Aubrey H, ....- (SanDiego : Elsevier, 2019)
"Since the first edition of Handbook on Animal-Assisted Therapy published, the field has changed considerably. The fifth edition of the Handbook highlights advances in the field, with 7 new chapters and over 75% revised. In reading this book, therapists will discover the benefits of incorporating animal assisted therapy into their practice, how to design and implement animal assisted interventions, and the efficacy of animal assisted therapy with different disorders and patient populations. Coverage includes the use of AAT with children, families, and the elderly, in counseling and psychotherapy settings, and for treating a variety of specific disorders"
Keywords: Therapie ; dieren